Chemometric analysis of GC-MS chemical profiles and biological activities of three citrus essential oils in Indonesia - Einstivina Nuryandani, Erliana Novitasari, Muhammad Fatih Abdurrahman, Nurul Habibi, Ardiba Rakhmi Sefrienda, Dedy Kurnianto, Jasmadi Jasmadi, Yusuf Andriana (Journal of Applied Pharmaceutical Science, 2024)
Citrus species essential oils (EOs) are significant sources of bioactive compounds and demonstrate diverse therapeutic effects. However, limited documentation exists regarding the phytochemicals associated with their biological activities. This study aims to assess the antioxidant activity, plant inhibitory properties, and brine shrimp cytotoxic effects of EOs derived from three Citrus species: C. sinensis, C. limon, and C. hystrix. Utilizing chemometric analysis and gas chromatography-mass spectrometry (GC-MS) fingerprints, the volatile components contributing to antioxidant activity were elucidated. The peels of the Citrus samples were hydro-distillated to obtain EOs, and subsequently subjected to antioxidant, plant inhibitory, and brine shrimp cytotoxic assays. The results indicated that C. limon EO exhibited the highest antioxidant activity, while C. hystrix and C. sinensis EOs demonstrated pronounced inhibitory effects against Artemia salina and Lactuca sativa, respectively. GC-MS analysis facilitated the identification of key compounds in each EO. Principal component analysis and hierarchical cluster analysis effectively categorized Citrus EOs based on their antioxidant properties, highlighting the proximity of C. limon and C. sinensis. Among the identified compounds, D-limonene, α-terpineol, caryophyllene, (+)-3-carene, β-pinene, (-)-spathulenol, trans-p-mentha-1(7),8-dien-2-ol, and trans-verbenol were the most discriminating compounds affected the antioxidant activity of C.limon and C. sinensis EOs.
Keywords: Citrus species, principal component analysis, essential oils, antioxidant activity, phytotoxic and cytotoxic effects, chemometric analysis